HIGHER EDUCATION GRADUATES’ UNEMPLOYMENT AND ITS DETERMINANTS - Puspitasari, Angela Shinta (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This study aims to capture the determinants of graduate unemployment in Indonesia by including macroeconomic factors such as inflation, trade openness, GDP per capita, and foreign direct investment. We utilize panel data used from 33 provinces in Indonesia between 2010 to 2020. The fixed effect model is employed to estimate the effect of these independent variables on graduate unemployment. The result shows a significant relationship between graduate unemployment and trade openness, GDP per capita, and foreign direct investment.